2002
DOI: 10.1207/s15327698jfc0204_01
|View full text |Cite
|
Sign up to set email alerts
|

Family Communication, Maternal and Paternal Expectations, and College Students' Suicidality

Abstract: This study extends current research on family communication and suicide risk in 2 ways. First, it examines variables that reflect communication patterns found in generally well-functioning families, as opposed to more commonly specified pathological factors, to assess the relationship of family communication and suicidality (ideation and attempts). Second, it examines the differential effects of family communication and parental expectations across gender, analyzing mothers and fathers separately. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 46 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…One reason females are more likely to experience suicidal ideation may be explained by family communication. For example, Miller and Day (2002) found that female suicidal ideation was linked to a particular pattern of family communication. The researchers focused on family communication and suicidality among college students.…”
Section: Suicide and Suicidal Behaviormentioning
confidence: 99%
“…One reason females are more likely to experience suicidal ideation may be explained by family communication. For example, Miller and Day (2002) found that female suicidal ideation was linked to a particular pattern of family communication. The researchers focused on family communication and suicidality among college students.…”
Section: Suicide and Suicidal Behaviormentioning
confidence: 99%
“…Despite holding these expectations, conformity orientation was not associated with actual perceived maintenance behavior. The combination of conformity orientation and holding high expectations in the parent-child relationship has been associated with negative outcomes such as suicide ideation among young adults (Miller & Day, 2002). Future research should further explore the influence of high conformity orientation and sibling expectations on the sibling relationship as research on conformity orientation among siblings is still in its infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have also found mental health disorders contributed to the majority of completed suicides among youth (Houston et al, 2001). A mental health approach represents one dominant narrative that frames suicidality in relation to an individual's deficiency (Marsh, 2015; Miller & Day, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%